2022
DOI: 10.1128/spectrum.01656-22
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Ideal Reference Genes for Gene Expression Analysis in COVID-19 and Mucormycosis

Abstract: Gene expression studies are critical to develop new diagnostics, therapeutics, and prognostic modalities. However, accurate determination of expression requires data normalization with a reference gene, whose expression does not vary across different disease stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Second, both host factors (previous infection history) and viral factors (different SARS-CoV-2 variants) may have had a significant impact on the dynamics of viral load, which in turn may have influenced the effectiveness of nasal irrigation [5]. In addition, considering the significant variations in Ct values that are commonly observed across COVID-19 patient groups, it would be important to adjust our results by the corresponding content of the house keeping gene [36]. Another important consideration with respect to the measurement of SARS-CoV-2 viral RNA is the discrimination between infectious and inactivated viral particles so as to decrease false-positive result rates.…”
Section: Discussionmentioning
confidence: 99%
“…Second, both host factors (previous infection history) and viral factors (different SARS-CoV-2 variants) may have had a significant impact on the dynamics of viral load, which in turn may have influenced the effectiveness of nasal irrigation [5]. In addition, considering the significant variations in Ct values that are commonly observed across COVID-19 patient groups, it would be important to adjust our results by the corresponding content of the house keeping gene [36]. Another important consideration with respect to the measurement of SARS-CoV-2 viral RNA is the discrimination between infectious and inactivated viral particles so as to decrease false-positive result rates.…”
Section: Discussionmentioning
confidence: 99%
“…CYP belongs to the immunophilin family and has peptidyl-prolyl cis - trans isomerase (PPIase) activity, which catalyzes the cis - trans isomerization process of proline residues. CypA demonstrated the most consistent expression irrespective of disease severity and emerged as the most suitable reference gene in COVID−19 and CAM [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…One notable example is the identification of DPP9, which is correlated with an elevated risk of developing severe illness due to COVID-19. [15] In addition, a recent study recognized interleukin 10 receptor subunit beta (IL10RB) as the primary candidate gene target for COVID-19 susceptibility. This study revealed an essential link between IL10RB, infection, and outcomes, highlighting it as the most promising candidate gene for further in-depth investigation.…”
Section: Genetic Factors Influencing Susceptibility To Covid-19mentioning
confidence: 99%
“…One notable example is the identification of DPP9 , which is correlated with an elevated risk of developing severe illness due to COVID-19. [15]…”
Section: Genetic Factors Influencing Susceptibility To Covid-19mentioning
confidence: 99%